Delayed antibiotic prescription for upper respiratory tract infections in children under primary care: Physicians' views. (2nd October 2017) - Raft, Camilla Flintholm; Bjerrum, Lars; Arpi, Magnus; Jarløv, Jens Otto; Jensen, Jette Nygaard
Abstract: Background: Overprescribing antibiotics for common or inaccurately diagnosed childhood infections is a frequent problem in primary healthcare in most countries. Delayed antibiotic prescriptions have been shown to reduce the use of antibiotics in primary healthcare. Objective: The aim was to examine primary care physicians' views on delayed antibiotic prescriptions to preschool children with symptoms of upper respiratory tract infections (URTIs). Methods: A questionnaire was sent to 1180 physicians working in general practice in the Capital Region of Denmark, between January and March 2015. The questions focused on physicians' attitude and use of delayed antibiotic prescriptions to children with URTIs. Results: The response rate was 49% ( n  = 574). Seven per cent of the physicians often used delayed prescriptions to children with symptoms of URTI, but 46% believed that delayed prescription could reduce antibiotic use. The physicians' views on delayed antibiotic prescription were significantly associated with their number of years working in general practice. Parents' willingness to wait-and-see, need for reassurance, and knowledge about antibiotics influenced the physicians' views. Also, clinical symptoms and signs, parents' willingness to shoulder the responsibility, the capability of observation without antibiotic treatment, and structural factors like out-of-hour services were relevant factors in the decision. Conclusions: Most physicians, especially those with fewer years of practice, had a positive attitude towards delayed antibiotic prescription. Several factors influence the views of the physicians—from perceptions of parents to larger structural elements and years of experience.